Analisis Transparansi Keuangan Publik di Era Digital: Studi Kasus KPPN Tanjungpinang - Hafifa, Nur; Erlisya, Vyona; Umaira, Putri Nabilah; Pangestoeti, Wahjoe (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Public financial transparency is one of the core principles of good governance. In the digital era, transparency is increasingly accelerated through the use of information and communication technology, including social media. This study aims to analyze how KPPN Tanjungpinang, as one of the technical implementation units of the Ministry of Finance, leverages social media to enhance transparency in public financial management. The data in this study were collected through an in-depth literature review, including an analysis of the official social media posts of KPPN Tanjungpinang, public financial reports, and e-government principles. The results show that KPPN Tanjungpinang actively disseminates public financial information, such as state budget realization, budget allocations, and work programs, through social media platforms. This strategy not only improves institutional accountability but also strengthens relationships with the public.